The Strength and Fatigue Life analysis of Sedan Car Ramp of The Ferry Ro-Ro 5000 GT Using Finite Element Method - Alamsyah, Alamsyah; Nurcholik, Samsu Dlukha; Suardi, Suardi; Pawarah, M U; Jumalia, Jumalia (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2021)
The Ferry Ro-Ro 5000GT has three levels of car deck that are connected by internal ramps. Two issues that have to be paid attention during the operation of the internal ramp there are the strength capacity and the design fatigue life of the internal ramp structure. The purpose of the research is to determine the strength and fatigue life of the internal ramp construction. The method used the Finite Element Method using a static load by load case of point load at top girder and between girders. Results of the research detected the maximum stress value is in the load case of the point load (three sedan car) at between of the girder is 52.143 MPa with the fatigue life is 44.47 years with the load cycle is 7300000 cycle while the minimum stress value detected at the load case of the point load (two sedan cars) at top girder is 34.199 MPa with the fatigue life is 195.92 years with the load cycle is 50000000 cycle. For the safety factor, ramp construction 6.08 ~ 10.38. The safety factor value above is still in safe condition because the value is SF > 1.